The Effect of Sodium Alginate-Coated Nano-Zinc Oxide on the Growth Performance, Serum Indexes and Fecal Microbial Structure of Weaned Piglets - Xiao Xiao; Kai Guo; Jinsong Liu; Yulan Liu; Caimei Yang; Yinglei Xu; Bo Deng (Animals, 2023)
High dose of zinc oxide (ZnO) could improve growth performance and alleviate disease status, whereas it caused serious environmental pollution and bacterial resistance. This study was to investigate whether low doses of sodium alginate-coated nano zinc oxide (saZnO), a new type of zinc resource, could serve as a potential alternative to pharmacological doses of traditional ZnO in weaned piglets. A total of 144 crossbred piglets were randomly allocated into three groups, including a basal diet without the addition of Zn (CON), a basal diet with 1600 mg Zn/kg from traditional ZnO (ZnO), and a basal diet with 500 mg Zn/kg from saZnO (saZnO). The experiment lasted for 28 days. The results showed that supplementing with ZnO and saZnO for 14 and 28 days significantly improved body weight (BW) and average daily gain (ADG) (p < 0.01) and markedly reduced the feed intake-to-gain ratio (F/G) (p < 0.05) and diarrhea rate. In addition, dietary ZnO and saZnO significantly increased the activities of the total antioxidant capacity (T-AOC) and alkaline phosphatase (ALP) (p < 0.01). Supplementing with saZnO also promoted the levels of superoxide dismutase (SOD), IgM and copper- and zinc-containing superoxide dismutase (Cu/Zn-SOD) in serum (p < 0.05), whereas a ZnO addition decreased the concentration of malondialdehyde (MDA) (p < 0.05), indicating the beneficial effect of Zn on antioxidant and immune functions. Piglets fed the ZnO diet showed higher serum Zn accumulations than those fed the CON and saZnO diets at d 28 (p < 0.01), and supplementing with ZnO and saZnO markedly contributed to Zn excretion in feces, especially in the ZnO diet (p < 0.01). Additionally, piglets fed the saZnO diet had greater valeric acid concentrations (p < 0.05) in their feces, while other short chain fatty acids (SCFAs) were not affected by different treatments (p > 0.05). Microbial alpha diversity was reduced in the saZnO group compared with the CON group (p < 0.05), while an obvious separation of microbial composition, the marker of beta diversity, was shown among the three groups (p < 0.05). At the genus level, six genera, including Clostridium_sensu_stricto_1, Terrisporobacter, f_Muribaculaceae, Subdoligranulum and Intestinibacter, were pronouncedly increased in the ZnO and saZnO groups (p < 0.05); another nine species were dramatically downregulated, such as f_Lachnospiraceae, f_Prevotellaceae, f_Butyricicoccaceae and f_Ruminococcaceae (p < 0.05). Finally, a functional analysis indicated that altered microbes significantly changed the “Metabolism” pathway (p < 0.05). These findings suggested that saZnO could act as a feasible substitute for ZnO to reduce Zn emission and enhance growth performance, antioxidant and immune functions, and to adjust the structure of gut microbiota in piglets.